L’appareil photo entre les mains d’auxiliaires de puériculture. Recherche-action en images et partage des compétences - Irène Jonas (Images du Travail, Travail des Images)
The use of photographs in a group meeting research contributed to the development of reflexivity and collective learning. Il encouraged exchanges between child care assistants team and researchers. Theses exchanges are based on the difference of how they tell about their job and how they show about it with still pictures. It brinks interesting debate on their professional skils.